Biological variation of total thyroxine (T4), free T4 and thyroid-stimulating hormone in 11 clinically healthy cats. Issue 6 (June 2021) - Jordan, Anne; Gray, Rachael; Terkildsen, Michael; Krockenberger, Mark
Objectives: The aim of this study was to investigate the biological variation of total thyroxine (T4), free T4 (fT4) and thyroid-stimulating hormone (TSH) in 11 clinically healthy cats aged between 3 and 15 years old, in Sydney, Australia. Methods: Blood was collected weekly for up to 6 weeks and serum T4, fT4 and TSH concentrations were analysed using canine-specific reagents. Restricted maximum likelihood was used to estimate within-subject, between-subject and analytical variance components, which were recorded in terms of the related coefficients of variation. The index of individuality and reference change values were then calculated for each analyte. Results: T4 and TSH had intermediate individuality, indicating both subject-based and population-based reference intervals (RIs) could be used, with the knowledge that population-based RIs are suboptimally sensitive. fT4 had high individuality, indicating subject-based RIs are more appropriate than population-based RIs. Conclusions and relevance: This study has demonstrated that subject-based RIs could be more sensitive than population-based RIs for the diagnosis of thyroid dysfunction in cats.